Developing better understanding on tropical peat fire occurrences and dynamics. (November 2019) - Putra, E I; Cochrane, M A.; Saharjo, B H; Graham, L; Thomas, A; Applegate, G; Saad, A; Setianto, E; Sutikno, S; Prayitno, A
Abstract: Peatland fires are a significant contributor to Indonesia's greenhouse gas (GHG) emissions, particularly during ENSO events, in drained areas, and upon first and second burns. This NASA-funded project will provide the necessary fire emissions research and expertise to increase capability of peatland fire emission quantification. The first three years of the project (2014-2017) focused on the development of methods to assess peat-fire relations and improve peat fire emission calculations, with initial data from the core area; BOSF-Mawas in Central Kalimantan. The second phase of the project (2017-2020) expanding to a national level to better advance Indonesia's capabilities for peatland carbon emissions, increasing the data volume and knowledge in the core area, and on transplanting these methods to other peatland provinces in Indonesia, e.g., Riau and Jambi. Here, we establish and monitor dipwells and subsidence plots in Central Kalimantan, Riau, and Jambi to better understand the effect of hydrology to the peat fire. To better understand the peat fire typology and dynamics, we develop the new method for Fire Scene Evaluation and measured some peat and peat fire properties. This paper compiling the project overview, researches have been done and on-going researches in Central Kalimantan, Riau, Jambi, and Papua provinces, and some essential findings of the project.